Enhancing Islamic banking and finance in South East Asia through the application of artificial intelligence: an exploration of banking’s best practices - Mohd. Zain, Nor Razinah; Ismail, Azman; Hassan, Rusni (2018)
The disruption of innovations through technology in the banking and finance sectors continues to indicate a positive trend among bankers, practitioners, and customers at large. Advantageous with speediness and fast track transaction, the innovations of technology support the spread in using banking and finance system without barriers of time and space. Recently, the banking and finance industry continues to be surprised by the latest technology’s innovation that is known as artificial intelligence or can be simply known as A.I. By looking into the ecosystem for the future sustainability of Islamic banking and finance in South East Asia, Islamic banking and finance may learn and adopt several best practices of A.I. from global banking practices. An exploration of the advantages of A.I. and readiness of the Islamic banking and finance industry in South East Asia must be looked into without fail. This research will also look into the attitudes of Islamic banks’ leadership in South East Asia in accepting A.I. Depending on secondary data collected by previous studies, this research depends on the qualitative investigation from documentary materials from Islamic and conventional banking and finance industry. As identified, A.I. stands with several advantages to the Islamic and finance industry in South East Asia. Even though the leadership of Islamic banks shows their readiness towards accepting the technology’s innovation or A.I., they are still tied down to the regulatory requirements, the readiness of their employees, acceptance of their shareholders, and awareness of their customers. HSBC seems to be at the front sit in implementing technology’s innovation of A.I. This research explores the best practices of implementing A.I. in the banking and finance industry that may be adopted by the Islamic banking and finance industry in South East Asia. It also identifies the trend of leadership in the said industry in facing the disruption of technology.